Analisis Faktor-Faktor Minat Mahasiswa dalam Menggunakan Produk Bank Syariah: Studi Kasus: Mahasiswa Universitas Teknologi Digital - Saepulloh; Komala, Neng Cahya (Ikatan Da'i Indonesia, 2024)
Banking in Indonesia is still the main means for people to carry out economic activities and other activities related to finance. Islamic banks provide services based on the concept of very modern and advanced financial transactions and the concept of justice. Currently, students are one of the people who are familiar with banking products and almost all of them use banking products. Students at the Digital Technology University are the majority Muslim, but most of the products used by Digital Technology University students are Conventional bank products. The research method used in this research is a qualitative method. The data collection technique in this study was to interview 15 respondents, namely Digital Technology University students. The results of this study were 10 out of 15 respondents used Conventional Banks because their interest was influenced by locations closer to Conventional Banks than Islamic Banks, lack of understanding of Islamic finance and the surrounding environment that mostly used Conventional Banks.